78.4k views
5 votes
F(n)=5xf(n-1)

f(0)=5

f(3)=



(x means multiple)

F(n)=5xf(n-1) f(0)=5 f(3)= (x means multiple)-example-1
User Loislo
by
5.9k points

2 Answers

4 votes

Answer:


\displaystyle 625

Step-by-step explanation:

All results are quintupled the previous terms:


\displaystyle 5 = f(0) \\ 25 = f(1) \\ 125 = f(2) \\ 625 = f(3)

I am joyous to assist you anytime.

User Mykhal
by
5.6k points
2 votes

Answer:

625

Step-by-step explanation:

So this says the following:

A term is equal to 5 times the previous term.

We are given the 0th- term is 5.

The first term is 5(5)=25.

The second term would be 5(25)=125.

The third term would be 5(125)=625.

So f(3)=625.

If you didn't like that explanation, you can find f(3), by first finding f(1) then f(2) using the equation given as is without making the interpretation I did above.


f(n)=5 \cdot f(n-1) ; plug in 1 for
n:


f(1)=5 \cdot f(1-1)


f(1)=5 \cdot f(0)


f(1)=5 \cdot 5


f(1)=25


f(n)=5 \cdot f(n-1) ; plug in 2 for
n:


f(2)=5 \cdot f(2-1)


f(2)=5 \cdot f(1)


f(2)=5 \cdot 25


f(2)=125


f(n)=5 \cdot f(n-1) ; plug in 3 for
n:


f(3)=5 \cdot f(3-1)


f(3)=5 \cdot f(2)


f(3)=5 \cdot 125


f(3)=625

User Dave Briand
by
6.3k points